THE INFLUENCE OF THE ON-TIME PERFORMANCE, FLIGHT SCHEDULES, TICKET PRICES, AND PASSENGER SATISFACTION IN DETERMINING CUSTOMER LOYALTY IN INDONESIAN GARUDA AIRLINES - Siti Ghumaisa Effendie; Suharto Abdul Majid; Indra Setiawan; Dian Artanti Arubusman; Yana Tatiana (International Journal of Social Science, 2025)
Some economic and agro-industrial managerial problems are that the company's human resources are not maximized in optimizing productivity, cost efficiency, and product quality control. This also includes improving understanding of markets, marketing strategies, and the development of appropriate technologies to improve agro-industrial performance. The purpose of this study is to examine the impact of on-time performance, flight schedules, and ticket prices on customer satisfaction and customer loyalty of Garuda Indonesia Airlines at Soekarno-Hatta International Airport Jakarta, Indonesia. The data collection method uses a questionnaire distributed to 100 respondents. The data analysis method uses SEM PLS. The results show that a positive and significant direct impact on customer satisfaction is obtained from on-time performance and ticket prices, while flight schedules have a positive and insignificant direct impact. A positive and significant direct impact on passenger loyalty, it is obtained from customer satisfaction and ticket prices, while on-time performance and flight schedules have a positive and insignificant direct impact, which implies that customer satisfaction is a vital factor for Garuda Indonesia Airlines to survive in such a highly competitive aviation market